A revision of the Australian genus Trachylestes with the description of two new species (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) - Malipatil, M.; Kwak, M.; Gunawardene, Nihara (Magnolia Press, 2016)
Copyright © 2016 Magnolia Press.Two new species, Trachylestes barrowensis sp. nov. from Barrow Island, Western Australia and T. queenslandensis sp. nov. from southeastern Queensland are described, and a key for their separation from other known species of the Australian endemic genus Trachylestes StÅl, 1868 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) is given.